The Effectiveness of Ledp Application on Students Listening Comprehension - Monica, Elsa; Izzah, Lidiyatul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThis research was aimed to measure the effectiveness of Listen English Daily Practice (LEDP) application in the improvement of 8th graders’ listening comprehension skills. There were 34 students comprised in one class involved as the sample of this study. This research used quantitative method with experimental approach and one-group pretest post-test design. In collecting the data, 20 multiple-choice questions in the pre-test and post-test were used as the instruments after the students were instructed to listen to conversation videos taken from YouTube. Data analysis of paired sample test was used in analyzing the data. That data analysis showed that the average score gained by the students in the post-test (82.20) was higher than the one in the pre-test (49.70). Besides, the calculation by using paired-sample test revealed that the standard error mean made by the students in the pre-test was 1.606 while in the post-test was 1.371. These findings showed that the errors made by the students in the post-test was smaller than in the pretest. The correlations between LEDP application as variable X and students’ listening comprehension skills as variable Y computed through paired-sample correlations indicated significant value of 0.01 which was lower than 0.05 (Sig. 0.01<0.05); meaning that the two variables were correlated. Therefore, this research rejected H0 and accepted Ha. To conclude, LEDP was an effective application utilized in improving students’ listening comprehension skills.Keywords: LEDP application, listening comprehension, application as teaching mediaAbstrak Penelitian ini bertujuan untuk mengukur efektivitas dari aplikasi Listen English Daily Practice (LEDP) pada peningkatan keterampilan pemahaman menyimak siswa kelas 8. Terdapat 34 orang siswa dalam 1 kelas yang dilibatkan sebagai sampel. Penelitian ini menggunakan metode kuantitatif dengan pendekatan ekperimen dan disain one group pre-test post-test. Dalam mengumpulkan data, 20 pertanyaan pilihan berganda pada pre-test dan post-test digunakan sebagai instrument dengan terlebih dahulu meminta siswa untuk menyimak topik percakapan yang peneliti ambil dari YouTube. Analisa data statistic paired-sample test digunakan dalam menganalisa data. Hasil Analisa tersebut menunjukkan capaian nilai rerata siswa pada post-test (82,20) lebih tinggi daripada nilai rerata pre-test (49,70). Selain itu, perhitungan menggunakan paired-sample test menunjukkan bahwa standar rerata kesalahan pada pre-test asalah 1,606, sedangkan pada post-test adalah 1,371. Hal ini berarti kesalahan siswa pada post-test lebih rendah daripada pre-test. Korelasi antara LEDP sebagai variabel X dengan keterampilan pemahaman menyimak sebagai variabel Y yang dihitung melalui paired-sample correlations menunjukkan nilai signifikan 0,01 lebih rendah dari 0,05 (Sig. 0,01<0,05) yang berarti terdapat korelasi antara kedua variabel tersebut. Dengan demikian, hasil penelitian ini menolak H0 dan menerima Ha. Sebagai kesimpulan, LEDP merupakan aplikasi yang efektif dalam meningkatkan keterampilan pemahaman menyimak siswa. Kata Kunci: aplikasi LEDP, pemahaman menyinak, aplikasi sebagai media ajar